Argent, valeurs et éthique dans le monde entrepreneurial de l’Espagne des années 1980 - Chantal Chartier (Cahiers de Civilisation Espagnole Contemporaine)
The present study deals with the 1980’s changes in mentality occurring in Spain at a time of economic boom following the country’s entry into the European Economic Union, which was characterised by Felipe González’s socialist government’s neo-liberal policies. This paper aims at analysing potential shifts in attitudes towards money and how resulting new values were being accounted for. References to Spain’s history appearing in the then Minister of the economy Carlos Solchaga’s public announcements or in articles taken from the economic press would concur and give grounds for the country’s economic backwardness and the catch-up phase in Spanish capitalism. Such references, by going beyond Spain’s anti-Calvinist dogmas and into a Catholic interpretation of capitalism –as in Ramiro de Maeztu’s work– can be traced back to Max Weber’s ideas on the spirit of Catholicism and the Protestant ethic.